Pengawasan Praktik Manipulasi Harga Dalam Perdagangan Digital Oleh Lembaga Persaingan Usaha Di Indonesia - Mahareni Puspa Arum; Tuhana Tuhana (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The development of the modern economy, which is characterized by digital trade through various buying and selling platforms, is not free from monopolistic practices, especially price manipulation behaviour by business actors, which is detrimental to consumers and other business actors. This matter needs to receive attention from business competition institutions to maintain healthy business competition. This writing aims to determine the extent of the KPPU's role as a business competition institution in supervising price manipulation practices in digital trade. The research method used is normative juridical which is prescriptive in nature by collecting primary and secondary legal materials to answer problems. From the research results, it was found that in the development of digital trade in Indonesia, an active role from the government is needed to update regulations that regulate in detail regarding monopolistic actions in the form of price manipulation in digital trade. It is hoped that the KPPU's role as a business competition supervisory institution will dynamically be able to balance the supervision of trade monopoly practices in the digital economy era.